STRATEGY OF THE DEPARTMENT OF COOPERATIVES, SMALL AND MEDIUM ENTERPRISES, INDUSTRY, AND TRADE OF MEDAN CITY IN ENFORCING THE PROHIBITION OF IMPORTED SECOND-HAND CLOTHING - Jana Raymond; R. Sally Marisa Sihombing (Indonesian Journal of Social Sciences, Policy and Politics, 2026)
The circulation of imported second-hand clothing has become a persistent challenge in many developing cities, including Medan City, Indonesia, due to its implications for public health, environmental sustainability, and the competitiveness of local small and medium enterprises. This study aims to analyze the strategy of the Office of Cooperatives, Small and Medium Enterprises, Industry, and Trade of Medan City in implementing the policy on the prohibition of imported second-hand clothing, with a particular focus on community economic empowerment. The research employs a qualitative descriptive approach, utilizing in-depth interviews, direct observations, and document analysis to capture institutional practices and stakeholder experiences. Data were analyzed using the strategic framework developed by Geoff Mulgan, encompassing purposes, directions, and actions. The findings indicate that although the policy objectives emphasize the protection and empowerment of local enterprises, the implementation faces significant challenges. These include weak data-based planning, limited coordination and communication among internal units and external stakeholders, and fragmented empowerment programs that are not aligned with the actual needs of affected traders. Training activities are often conducted without adequate follow-up support, such as access to capital, business mentoring, or market facilitation, resulting in limited long-term impact. The study concludes that the effectiveness of the strategy remains constrained by structural and managerial weaknesses. This research highlights the need for an integrated, participatory, and sustainable empowerment approach that combines capacity building, financial access, and institutional collaboration to support local economic resilience and sustainable urban development.